The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21836/pem20160503
|View full text |Cite
|
Sign up to set email alerts
|

The use of positive end-expiratory pressure (PEEP) and alveolar recruitment manoeuvre (ARM) in equine anaesthesia – a review

Abstract: Summary: Impairment of gas exchange and arterial oxygenation during general anaesthesia and recumbency of the horse are a common and well-known problem. Often these alterations are poorly responsive to intermittent positive pressure ventilation (IPPV) and increasing levels of supplemental oxygen. Over the last decades the understanding of the underlying pathophysiology developed more and more, recognizing that a decrease in functional residual capacity (FRC), lung collapse and atelectasis, and ultimately venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…It is generally considered that mechanical ventilation should better be started early after induction of general anaesthesia to avoid large areas of lung atelectasis 12 , which may make recruitment more difficult. 41 This probably partially explains the failure of standard mechanical ventilation to improve the situation and delays the success of recruitment manoeuvres in the present case. A previous study suggests that mechanical ventilation with PEEP initiated from the beginning of anaesthesia is more effective to decrease development of atelectasis and hypoxaemia.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It is generally considered that mechanical ventilation should better be started early after induction of general anaesthesia to avoid large areas of lung atelectasis 12 , which may make recruitment more difficult. 41 This probably partially explains the failure of standard mechanical ventilation to improve the situation and delays the success of recruitment manoeuvres in the present case. A previous study suggests that mechanical ventilation with PEEP initiated from the beginning of anaesthesia is more effective to decrease development of atelectasis and hypoxaemia.…”
Section: Discussionmentioning
confidence: 75%
“…Half an hour of standard mechanical ventilation did not improve the situation; rather, the values worsened revealing the extent of V/Q mismatch and pulmonary shunt. It is generally considered that mechanical ventilation should better be started early after induction of general anaesthesia to avoid large areas of lung atelectasis 12 , which may make recruitment more difficult 41 . This probably partially explains the failure of standard mechanical ventilation to improve the situation and delays the success of recruitment manoeuvres in the present case.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have demonstrated that the degree of alveolar collapse can be reduced by application of an alveolar recruitment manoeuvre (ARM) and continuous PEEP [16,27,28]. An alternative approach consists of an ARM provided by stepwise incremental and decremental peak inspiratory pressure (PIP) and PEEP, which has been found to be amongst the most effective methods to redistribute ventilation and improve oxygenation [29,30]. Additional strategies involve the use of continuous CPAP, which also proved effective in redistributing ventilation to the dependent lung regions, thereby decreasing ventilation/perfusion mismatch [23].…”
Section: Discussionmentioning
confidence: 99%
“…PEEP increases functional residual capacity (FRC) over the critical closing volume, hence helping prevent alveolar collapse at the end of expiration 23,27 . While application of PEEP without an ARM did not prove effective in improving gas exchange in spontaneously breathing anaesthetised horses, 28 it was demonstrated to change distribution of ventilation and increase PaO 2 and FRC when mechanical ventilation was used 29–31 .…”
Section: Discussionmentioning
confidence: 99%
“…PEEP increases functional residual capacity (FRC) over the critical closing volume, hence helping prevent alveolar collapse at the end of expiration. 23,27 While application of PEEP without an ARM did not prove effective in improving gas exchange in spontaneously breathing anaesthetised horses, 28 it was demonstrated to change distribution of ventilation and increase PaO 2 and FRC when mechanical ventilation was used. [29][30][31] Nonetheless, high levels of PEEP are associated with high intrathoracic pressures, which may decrease the ventilation/perfusion ratio by forcing blood into already atelectatic lung areas, leading to a higher degree of right-to-left shunt and decreased oxygenation.…”
Section: Discussionmentioning
confidence: 99%